2020
DOI: 10.7554/elife.46775
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of synucleinopathic seeding by rationally designed inhibitors

Abstract: Seeding, in the context of amyloid disease, is the sequential transfer of pathogenic protein aggregates from cell-to-cell within affected tissues. The structure of pathogenic seeds provides the molecular basis and enables rapid conversion of soluble protein into fibrils. To date, there are no inhibitors that specifically target seeding of Parkinson’s disease (PD)-associated α-synuclein (α-syn) fibrils, in part, due to lack of information of the structural properties of pathological seeds. Here we design small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 34 publications
4
63
0
Order By: Relevance
“…The finding that the structures of α-synuclein filaments from MSA differ from those of assembled recombinant proteins is consistent with the observation that rationally designed aggregation inhibitors of α-synuclein reduced aggregation by MSA and recombinant filament seeds to different extents (71). This finding is also reminiscent of similar results for tau filaments (4-9), even though marked differences exist between tau and α-synuclein.…”
Section: Recombinant Alpha-synucleinsupporting
confidence: 87%
“…The finding that the structures of α-synuclein filaments from MSA differ from those of assembled recombinant proteins is consistent with the observation that rationally designed aggregation inhibitors of α-synuclein reduced aggregation by MSA and recombinant filament seeds to different extents (71). This finding is also reminiscent of similar results for tau filaments (4-9), even though marked differences exist between tau and α-synuclein.…”
Section: Recombinant Alpha-synucleinsupporting
confidence: 87%
“…12 This is reminiscent of enzyme kinetics, and elongation can be treated as a two-step enzymatic reaction, in which bril-end and monomer serve as catalyst and substrate, respectively. [19][20][21] Proteins and peptides have been designed to specically inhibit the elongation of aS brils, [22][23][24][25] e.g., by aiming to dock complementary b-strands onto the open b-sheets at the brilends, to prevent the catalytic site from guiding the conformational conversion of further monomers. However, understanding how monomers and inhibitors get incorporated at bril-ends is still a subject of active research.…”
Section: Introductionmentioning
confidence: 99%
“…Another relevant mechanism that contributes to the propagation of neurodegeneration is the prion-like spread of α-syn aggregates. Indeed, experimental studies revealed that the injection of α-syn inclusions in animal’s brain promotes the formation of cellular inclusions at the injection site from where they can spread in other brain regions 11 . To date, the therapies available for the treatment of PD are addressed to reduce the motor symptoms and include the administration of drugs able to restore the level of dopamine.…”
Section: Introductionmentioning
confidence: 99%